2016
DOI: 10.46792/fuoyejet.v1i1.8
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Shelf Life of Selected Sachet Water in Ogbomoso, Oyo State Nigeria

Abstract: Water is life and every living thing depends on it for existence. Sachet water has gradually become the most widely consumed liquid in Nigeria with varying qualities. This study investigates the temporal variation in water quality of Sachet water produced in Ogbomoso, Oyo State. Ten (10) brands of sachet water from Ogbomoso South and North Local government area were collected within 24 hours of production and stored at standard room temperature and conditions. Sub-samples were drawn from the stock samples on d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…A study by Omalu et al stated that sachet water is a common source of drinking water in urban areas due to its availability and affordability 20. Olaniyan et al found that reported reasons for sachet water intake are that it is cheaper, hygienic, pure and is considered safe 21…”
Section: Discussionmentioning
confidence: 99%
“…A study by Omalu et al stated that sachet water is a common source of drinking water in urban areas due to its availability and affordability 20. Olaniyan et al found that reported reasons for sachet water intake are that it is cheaper, hygienic, pure and is considered safe 21…”
Section: Discussionmentioning
confidence: 99%
“…The staff and students are not totally free from waterborne diseases through the consumption of sachet water. The safety of sachet water is entirely dependent on the water source, treatment, packaging and storage (Olaniyan et al 2016). Increasing rates of infectious and gastrointestinal diseases have also been discovered in schools where water and sanitation facilities are inadequate (Morgan et al, 2017).…”
Section: Water Supply Facilitiesmentioning
confidence: 99%
“…Potable water supply has become increasingly unavailable in Nigeria, thus creating a scarcity of this indispensable resource in many urban regions of Nigeria (Edema et al 2011;Olaniyan et al 2016). Hence, sachet-packed or bottled drinking water produced by water processing factories has become the readily available alternatives (Omalu et al 2010;Epundu et al 2017) for the supply of potable water in both urban and rural areas in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, sachet-packed or bottled drinking water produced by water processing factories has become the readily available alternatives (Omalu et al 2010;Epundu et al 2017) for the supply of potable water in both urban and rural areas in Nigeria. The sachetpacked drinking water, which refers to drinking water that is commercially packed in easy-to-open 50-60 millilitres polyethylene sac (Edema et al 2011), is relatively cheaper than the bottled water and is most widely consumed in Nigeria (Olaniyan et al 2016). However, sachet-packed drinking water is often not properly processed by the water processing factories and may contain unwanted microorganisms which upon prolonged storage at room temperature may grow to unacceptable levels that may expose potential consumers to probable adverse health effects (Oladipo et al 2009;Okeke et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation